CURAHAN WAKTU KERJA WANITA DALAM KELUARGA PETANI WORTEL DI KELURAHAN RURUKAN KECAMATAN TOMOHON TIMUR KOTA TOMOHON - Remin Dina Maradou; Martha Mareyke Sendow; Welson Marthen Wangke (AGRI-SOSIOEKONOMI, 2019)
The purpose of this study was to determine the outpouring of women's working time in the family of carrot farmers, in the form of activities in the family and outside the family for carrot farming. This research was conducted for four months from October 2018 to January 2019. The data used in this study were primary data and secondary data. Primary data is obtained through direct interviews based on a list of questions to all female carrot farmers, in research location, as many as 17 people both as land owners and as land borrowers who seek carrot farming and have a family. Secondary data was obtained from the Rurukan Village Office and the internet through the Google Scholar to obtain articles, journals, and thesis related to the topic of research on the outpouring of women's working time in the farmer's family. The analysis used is descriptive analysis and in table form. The results of the study showed that the total work time of women in the carrot farmer family in Rurukan Village, Tomohon Timur Sub-District in the largest one week in the type of work in the family by all respondents was 251 hours and an average of 14.76 per respondent, compared to outpouring time outside the family for carrot farming in one week by all respondents was 56.16 hours and an average of 3.30 per respondent.*eprm*